NILAI SOSIAL-EKONOMI AIR DI KAWASAN PURA TIRTA EMPUL DESA MANUKAYA, KABUPATEN GIANYAR, BALI: SUATU PENDEKATAN EKONOMI LINGKUNGAN - MADE SUDITA; MADE ANTARA (SOCA: Jurnal Sosial Ekonomi Pertanian, 2006)
Government Rule of the Republic of Indonesia No. 82, 1991, article 7 section 2concerning the Quality Management and the Control of Water Pollution stipulates that inplanning the use of water, it is obligatory to pay attention to economic and ecologicalfunctions, religious values, and traditions that obtain in local community. This will bringan influence to the system of the flow of run off and infiltration that serve as the mainsource of the reserve of underground water supply The same is true for the flow of uppercourse of Tukad Pakerisan river which serves as the catchment's area has been underpressure so that it can influence the debit of water source in the area of Tirta EmpulTemple. For this purpose, a study needs to be carried out in order to know the socialbenefit, total economic value, and the conservational effort that have been made by thecommunity and the Regency Government of Gianyar.Through the study of environmental economy with the approach of total economicvalues, what will be obtained is direct and indirect use value, selection and heritage values,as well existence values. By knowing the water values in the area of Tirta Empul Templewill could account social benefit and total economic value. According the result anddiscussion, the social benefit of water within the area of Tirta Empul Temple is Rp.782.199.620,00 per year and the total economic value of Rp 2.314.040.471,86 per year.Conservation effort that has been made by the community and the RegencyGovernment of Gianyar such as the conservation of the forest that belongs to Laba Pura(the temple's area), the making of forest for the community, and the activities for makingseeds for the local community. Based on that conclusion, it is suggested that in making theeffort for the preservation of the function of the water within the area of Pura Tirta Empulthat has important economic value so the development of catchment's area should bedirected towards the area of yearly plants culturing.